Note—Response to “Equilibrium Strategies for Final-Offer Arbitration: There is No Median Convergence” - Rabow, Gerald (Management Science, 1985)
For an arbitrator model different from the one in the referenced paper, final-offer arbitration (FOA) is very effective. This suggests that strategies for conducting successful FOA may be available to arbitrators. In the above quoted paper, Brams and Merrill (Brams, Steven J., Samuel Merrill, III. 1983. Equilibrium strategies for final-offer arbitration: there is no median convergence. Management Sci. 29 (August) 927–941.) quote a statement on final-offer arbitration (FOA): “The theory which underlies final-offer arbitration is quite simple. If the arbitrator or panel was permitted to select only one or the other of the parties' final offers, with no power to make a choice anywhere in between, it was expected that the logic of the procedure would force negotiating parties to continue moving closer together in search of a position that would be most likely to receive neutral sympathy. Ultimately, so the argument went, they would come so close together that they would almost inevitably find their own settlement.” and then refute it as follows: “One purpose of our article is to show that there is little truth to this theory: divergence, rather than convergence, of equilibrium strategies is the norm.”